Political Ecology: The Dynamics of Local Government in Sustainable Natural Resource Management (A Study of The Sand Mine on Tunda Island) - Panji Sion (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the dynamics of local government in sustainable natural resource management amid the expansion of marine sand mining activities on Tunda Island, Serang Regency, Indonesia. Using an empirical qualitative approach with a case study design, the research investigates how power relations, institutional arrangements, and resource access shape environmental governance outcomes within a coastal socioecological setting. Data were collected through in depth interviews, field observations, and document analysis involving fishers, village officials, community leaders, and policy observers. The findings reveal that local government actors functioned as strategic intermediaries that facilitated access to mining related benefits while simultaneously reproducing unequal patterns of resource control. The study also identifies significant governance gaps resulting from fragmented institutional authority, regulatory ambiguity, limited local oversight, and weak accountability mechanisms following shifts in governmental authority. These conditions contributed to ineffective environmental monitoring and constrained community participation in decision making processes. Ecological degradation, declining fish catches, social fragmentation, and increasing dependence on compensation emerged as major consequences of extractive governance. Community responses included resistance, adaptive livelihood strategies, and demands for environmental justice. The study argues that sustainable coastal governance requires stronger institutional coordination, participatory accountability mechanisms, and greater recognition of local ecological knowledge within resource management frameworks.